Occupational accidents with sharp tools among cleaning workers - Silmara Meneguin; Jairo Aparecido Ayres; Renata Kimie Morine (Universidade Federal de Santa Maria, 2015)
Aim: to analyze the profile of accidents with sharp tools involving cleaning workers at a university hospital in a city of São Paulo. Method: retrospective study in which 377 Occupational Accident reporting forms were used for the data collection, reported by outsourced cleaning workers at a university hospital in a city in the State of São Paulo, between January 2000 and December 2008.Results: 184 accidents were reported, an average of 1.70 per month, predominantly involving women (89.6%), between 21 and 39 years of age (69%). The highest incidence was registered at the nursing wards (39.7%), during the day (75.4%) and mainly with needles (65.3%). Conclusions: these findings underline not only the need to implement effective prevention programs for accidents involving sharp tools, but also to recognize individual and institutional factors involved in the process, in order to guarantee safer hospital practices